Is psychosocial and cognitive dysfunction misattributed to the virus in hepatitis C infection? Select psychosocial contributors identified. Issue 8 (11th May 2016) - Lowry, D.; Burke, T.; Galvin, Z.; Ryan, J. D.; Russell, J.; Murphy, A.; Hegarty, J.; Stewart, S.; Crowe, J.
Summary: Chronic hepatitis C is associated with health‐related quality of life and cognitive impairments, even in mild disease. Recent evidence demonstrating hepatitis C virus (HCV) neurotropism has strengthened a neuropathophysiological hypothesis. However, sample heterogeneity confounds study outcomes. A uniquely homogeneous cohort of Irish women, following an iatrogenic HCV outbreak, offers a rare opportunity to control for HCV chronicity and the virus' purported impact on quality of life and cognition. A multi site, three‐group, cross‐sectional design was employed. Noncirrhotic, iatrogenically infected women, developing either acute or chronic infection, were recruited from prospective tertiary‐care liver clinics and the community. Well‐matched healthy controls were also recruited. All participants completed a psychosocial survey and were invited to undergo a comprehensive neuropsychological test battery. Significantly distressed psychosocial symptom profiles were observed in those with an iatrogenic HCV exposure history, which was independent of viral chronicity. Chronic and cleared HCV cohorts were not differentiated from each other. Two distinct subgroups, demarcated along 'impaired' vs 'nonimpaired' quality‐of‐life reports, were clearly identified and logistic regression analysis identified depressed mood and cognitive fatigue, rather than viral status, as statistically significant predictors of group membership. Compared with matched controls, significant cognitive impairments were not observed in either HCV cohort. Our findings provide strong evidence of nonviral factors accounting for quality of life impairment in chronic HCV and they also appear to question existing reports of cognitive dysfunction in mild disease. Depressed mood and cognitive fatigue appear to be critical psychosocial mediators of reduced quality‐of‐life and we hypothesize that metabolite abnormalities reported in HCV samples may also be confounded by these factors, given the associated literature.